1993
DOI: 10.1021/bi00059a013
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of azurin from Pseudomonas aeruginosa and some of its methionine-121 mutants

Abstract: Azurin from Pseudomonas aeruginosa and two mutants where the methionine ligand has been mutated have been studied in order to directly investigate the functional and structural significance of this ligand in the blue copper proteins. Reduction potentials, X-ray absorption fine structure (XAFS), electron paramagnetic resonance (EPR), and optical spectra are obtained in an attempt to provide a direct correlation between the spectrochemical properties and the immediate structure of this redox center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 38 publications
7
65
1
Order By: Relevance
“…A closer approach of Gly45 C = O to the Cu ion than in wt Cu(I1) azurin has been observed, for instance, in the crystal structure of Zn azurin . A strengthening of the axial Cu-0 = C Gly45 interaction, which is weak in wt azurin (Nar et al, 1991b;Lowery and Solomon, 1992), is compatible with the observed changes of the All and gll values and of the wavelengths of the CT bands in the EPR and the optical spectra, respectively, of M44K azurin at high pH (Peisach and Blumberg, 1974;Karlsson et al, 1991;Pascher et al, 1993;Murphy et al, 1993;Romero et al, 1993). The observed shift of the 281-cm-' peak in the M44K-azurin RR spectrum by +4 cm-' (Fig.…”
Section: Spectroscopic Effects Of Lys44 Deprotonationmentioning
confidence: 53%
“…A closer approach of Gly45 C = O to the Cu ion than in wt Cu(I1) azurin has been observed, for instance, in the crystal structure of Zn azurin . A strengthening of the axial Cu-0 = C Gly45 interaction, which is weak in wt azurin (Nar et al, 1991b;Lowery and Solomon, 1992), is compatible with the observed changes of the All and gll values and of the wavelengths of the CT bands in the EPR and the optical spectra, respectively, of M44K azurin at high pH (Peisach and Blumberg, 1974;Karlsson et al, 1991;Pascher et al, 1993;Murphy et al, 1993;Romero et al, 1993). The observed shift of the 281-cm-' peak in the M44K-azurin RR spectrum by +4 cm-' (Fig.…”
Section: Spectroscopic Effects Of Lys44 Deprotonationmentioning
confidence: 53%
“…X-ray absorption spectra at the Cu and Zn K edges were measured in¯uorescence, again on SRS Station 9.2. Data-collection procedures have been described previously (Murphy et al, 1993). The EXAFS was normalized to a unit metal atom and extracted from the background absorption using the Daresbury Laboratory program EXBACK (Morrell et al, 1989).…”
Section: X-ray Fluorescence and Exafs Data Collectionmentioning
confidence: 99%
“…Since the copper ion is common, the structures of the copper binding sites must determine the chemical differences between the cupredoxins. Many structures have been determined for mutant (Nar et al, 1991b;Murphy et al, Cupredoxins include rusticyanin (RC), azurin from Alcaligenes denitrificans (AZAd ), cucumber basic protein (CBP), Plastocyanin from Populus nigra (PCPn ), pseudoazurin (cAZ), and amicyanin (AC). Secondary structure assignments were made using the algorithm of Kabsch and Sander (1983) as implemented in RIBBONS (Carson & Bugg, 1986) using the available three-dimensional coordinates for cupredoxins as defined in the legend to Figure 2.…”
Section: The Copper Binding Sitementioning
confidence: 99%